Penerapan Metode Least Square Pada Peramalan Penggunaan Naocl Pada Proses Produksi Di Unit KPB - Wardhani, Rachmasari Pramita; Norhidayah, Siti (LPPM Politeknik Jambi, 2025)
Companies engaged in processing including manufacturing industry must be oriented to the process in addition to production results, in this case the quality of the output must be improved or even maintained, this is to support services to the community of users of the production results. The selection of main raw materials and supporting raw materials and their needs must also be considered and must be right on target so that they can produce production as expected. The existence of forecasting is the one of important ways for companies to face future risks. Therefore, the preparation of the need for the use of Naocl materials in production must certainly be calculated so it will effective when use and efficient in financing. The method can be a method of forecasting the use of raw material needs because this method becomes the form of periodic series data’s that uses historical usage data in the past to forecast the next needs. The method used in this research is the method of quantitative descriptive by taking historical datas by using Naocl raw materials and then processing it using the least square method and obtaining forecast results in the 9th, 10th, 11th, and 12th months in 2023, then the data is processed again based on the annual amount for 2024 and 2025 based on data from 2020, 2021, 2022 and 2023. So the forecast for use in 2024 is 64446.3 liters and in 2025 it is 59662.4 liters from the equation Y = 88365.8 + (-4783.9) X. then the analysis result of the amount of Naocl usage can be predicted that the use of Naocl will decrease, it could be causing from the presence of other raw materials used, or the use of other equipment as support so as reduce using the chemicals material in production process.